Mobilising the Red Cross Journal: A Charity’s Periodical in Wartime - Marjorie Gehrhardt (Anglica. An International Journal of English Studies)
The first issue of the Red Cross Journal was published in January 1914, only eight months before the outbreak of the First World War. This article explores the impact of the war on this publication, as the work of the charity it represented dramatically expanded over the course of the conflict. How did the Journal survive the war, at a time when the Red Cross was deeply involved in supporting soldiers? This article examines the genesis of this publication and its evolving role during the war. This periodical, we argue, not only helped raise awareness of the work carried out by the Red Cross, but it also served practical purposes in the areas of training and funding. This publication reveals an increasingly critical stance towards the British Empire’s enemies in the war, as well as the need for the British Red Cross Society to foster a sense of unity amongst members posted around the world.